Developing social entrepreneurial intention: An intervention study in Thailand - SKUTALAKUL, Kanyaporn (Institutional Knowledge at Singapore Management University, 2022)
Social entrepreneurs are key players that could potentially create new initiatives and long-term solutions for our world to sustain the predicted forthcoming crises of overconsumption. Our world needs both kinds of entrepreneurship, both social and business, to collaboratively stimulate growth in a more balanced manner; however, the creation of social entrepreneurs at a higher rate of success and diffusion remains a challenge. This research proposed a number of new antecedents of social entrepreneurial intention (SEI) that were suggested by an exploratory study. The research was conducted in the context of Thailand and was designed to investigate the effects of different interventions on the relationships between SEI and its antecedents through a selected social entrepreneurship training program. This research effort lends support to the concern that the wholesale adoption of for-profit entrepreneurship practices may have overlooked some of the essential engines that could drive the level of commitment and resilience of potential social entrepreneurs. Two studies were conducted. The first study was a series of semi-structured interviews. Findings from these interviews led to a newly proposed model of SEI formation for the Thailand context. A second study was done employing a quantitative survey to investigate the effects of three types of training interventions (skill-based learning, community-based learning, and a hybrid of the two) on the intentions of would-be social entrepreneurs. Three insightful findings of this research were put forth: 1) Overcoming the early stage of venture formation, which is comprised of risk-taking capability and innovativeness, is crucial in increasing the social entrepreneurial intention of the would-be social entrepreneurs. 2) Perceived risk-taking capability is the most important predictor of social entrepreneurial intention. 3) Community-based learning has a positive moderating effect on the impact of risk-taking capability on social entrepreneurial intention, while skill-based learning has a negative moderating effect at such an early stage of social entrepreneurship. Within the Thai context, relationships with communities played an important role in potentially accelerating the risk-taking ability of would-be social entrepreneurs to engage in a social venture. In contrast, greater awareness of problems and solutions reduces risk-taking intention, and in-turn, reduces social entrepreneurial intention. This study contributes to the body of research on the antecedents that effect the development of social entrepreneurs and the potential efficacy of training interventions.